Correlation of coagulopathy and frozen elephant trunk use in aortic arch surgery: A systematic review and meta‐analysis. Issue 12 (22nd September 2021) - Bashir, Mohamad; Abo Aljadayel, Hadi; Mousavizadeh, Mostafa; Daliri, Mahdi; Rezaei, Yousef; Tan, Sven ZCP; Mohammed, Idhrees; Hosseini, Saeid
Abstract: Background: The advent of frozen elephant trunk (FET) for reconstruction of elective and nonelective aortic arch surgery has augmented the treatment of complex aortic pathologies in a single‐stage operation. To date, no studies have been focused on the prevalence and predictors of coagulopathy potentiated by FET procedure. Methods: In a systematic review, we searched databases up to June 2020 to find studies reporting coagulopathy complications after FET procedure. A proportional meta‐analysis was carried out using STATA software (StataCorp). Results: A total of 46 studies consisting of 6313 patients were eligible. The pooled estimation of reoperation for postoperative bleeding was 7% (95% confidence interval [CI:] 5–8; I 2  = 84.73%; reported by 39 studies including 4796 patients). The mean volume of transfused packed blood cells and fresh frozen plasma was 1677 ml (95% CI: 1066.4–2287.6) and 1016.5 ml (95% CI: 450.7–1582.3). The subgroup by the stent type showed a decrease in the heterogeneity ( I 2  = 0.01%, I 2  = 53.95%, I 2  = 0.01%, and I 2  = 54.41% for Thoraflex® Hybrid, E‐vita®, Frozenix®, and Cronus®, respectively). The subgroup by the chronicity of operation resulted in less heterogeneity among patients undergoing elective compared with nonelective operation ( I 2  = 29.22% vs. I 2  = 80.56% in nonelective). Meta‐regression analysis showed that age and male gender significantly impacted on the reoperation for postoperative bleeding. Conclusions: The FET procedure for arch replacement is associated with coagulopathy complications and the transfusion of blood products. Male, age, and selective choice of FET use were found to be the heterogeneity sources of reoperation for postoperative bleeding.